Confirming the Unusual Temperature Dependence of the Electric-Field Gradient in Zn - Heinz Haas; Dmitry Zyabkin; Juliana Schell; Thien T. Dang; Ian C. J. Yap; Ilaria Michelon; Daniel Gaertner; Adeleh Mokhles Gerami; Cornelia Noll; Reinhard Beck (Crystals, 2022)
The electric-field gradient (EFG) at nuclei in solids is a sensitive probe of the charge distribution. Experimental data, which previously only existed in insulators, have been available for metals with the development of nuclear measuring techniques since about 1970. An early, systematic investigation of the temperature dependence of the EFG in metals, originally based on results for Cd, but then also extended to various other systems, has suggested a proportionality to T3/2. However, later measurements in the structurally and electronically similar material Zn, which demonstrated much more complex behavior, were largely ignored at the time. The present experimental effort has confirmed the reliability of this unexpected behavior, which was previously unexplained.